Broadening Medical Students' Exposure to the Range of Illness Experiences: A Pilot Curriculum Focused on Depression Education. (January 2020) - Pandhi, Nancy; Gaines, Martha; Deci, David; Schlesinger, Mark; Culp, Cecilia; Karp, Zaher; Legler, Christie; Grob, Rachel
Abstract : Problem: Exposing medical students to a broad range of illness experiences is crucial for teaching them to practice patient-centered care, but students often have limited interaction with patients with diverse illness presentations. Approach: The authors developed, implemented, and evaluated a self-directed online curriculum followed by a small-group discussion focused on depression education. The curriculum was based on a module created using the Database of Individual Patients' Experiences methodology. Findings from 40 interviews with young adults across the United States about their diverse experiences with depression were summarized online, and the summaries were illustrated by video, audio, and text clips. From August 2016 to April 2017, third-year students completed either this online curriculum and the usual clerkship curriculum or just the usual clerkship curriculum. These intervention and control groups completed pre- and postsurveys. Outcomes: Students in the intervention group reported that the online curriculum influenced their thinking about depression (51/56) nearly as often as they reported that seeing patients in clinic did (53/56). They also reported greater decreases in personal stigmatizing attitudes toward depression than did students in the control group as measured by the Depression Stigma Scale (5.75–4.02, intervention; 6.50–5.65, control; P = .004). In open-ended responses, students in the intervention group were 13 times more likely to describe key lessons from the curriculum that reflected patient heterogeneity. Next Steps: Future collaborations include implementing and evaluating this curriculum at other medical schools and developing additional versions based on other illness experiences. Abstract : Supplemental Digital Content is available in the text.